Registration Information System for Real Work Practices (PKN) and Thesis Faculty of Engineering, University of Pancamarga - Attijani, Ahmad; Hikmah, Nuzul; Misdiyanto (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2022)
A website is a collection of pages containing certain information and can be accessed easily by anyone, anytime, and anywhere through the internet. In an educational institution, of course, it is very necessary for information systems  in  regulating  academic  activities  that  are  fast,  effective,  efficient,  accurate  to  improve  the  quality standards of education in these educational institutions.Faculty of Engineering, Panca Marga University is one of the private universities in Probolinggo Regency with 3 (three) study programs, namely electrical engineering, mechanical engineering and industrial engineering. Final projects such as Real Work Practice (PKN) and thesis are  the  final  tasks  that  must  be  completed  by  a  student  who  will  graduate  from  the  level  of  undergraduate education   or   diploma   in   college.Currently,   the   final   project   administration process   at   the   Faculty   of Engineering,  Panca  Marga  University  is  still  computerized  simply  where  the  final  task  implementation  data  is still  stored in  folders  made  by  academic  staff  themselves,  there is  no final  project  reporting  system.  This  is  felt inappropriate so it takes a long time to process the final project data with a large number of students. Based on this, researchers created a pkn final project information system and web-based thesis. In this study, the authors used  the  Waterfall  Method  as  an  application  development  method.  The  Waterfall  method  is  a  sequential development  model.  In  the  process  of  creating  the  waterfall  method,  it  starts  with  analysis,  design,  coding, testing and maintenance.